Explicit Numerical Solution of High - Dimensional Advection - Diffusion - Bayatmanesh, Elham (International Journal of Mathematical Research, 2013)
The Several numerical techniques have been developed and compared for solving the one-dimensional and three-dimentional advection-diffusion equation with constant coefficients. the subject has played very important roles to fluid dynamics as well as many other field of science and engineering. In this article, we will be presenting the of n-dimentional and we neglect the numerical examples.